FROM TRADITION TO TOURISM: SUSTAINABLE MANAGEMENT STRATEGY FOR RUTONG DIGITAL HERITAGE VILLAGE COMPETITIVENESS - Aunalal, Zany Irayati; Tangnga, Meiske Helena; Luturmas, Join Rachel; Hahury, Jessy Juniu; Titioka, Stenly Ronaldo; Siahaya, Joice (Politeknik Negeri Ambon, 2025)
Introduction: This research develops sustainable management strategies to enhance the competitiveness of Rutong Village as Indonesia's first digital tourism destination in the South Leitimur District, Ambon CityMethods: Employing a qualitative approach with SWOT-AHP analysis, the study engaged 15 key informants through in-depth interviews, participatory observation, and focus group discussions.Results: The analysis reveals critical internal factors, including natural beauty (68% coral coverage), rich cultural heritage (12 oral traditions, 6 traditional dances), and national recognition as a Digital Heritage Village (ADWI 2023), alongside challenges of limited accessibility, inadequate promotion, and seasonal dependence. External factors encompass government support opportunities, eco-tourism trends, and digitalization potential, while facing threats from destination competition, environmental degradation, and climate vulnerabilities. The research yields eight prioritized strategies, with SO1 (Integrated Tourism Attraction Enhancement) ranking highest, followed by SO2 (Strategic Partnerships), and WO1 (Sustainable Eco-Tourism Development). Implementation prioritizes strengthening unique cultural-natural synergies, developing strategic collaborations, and establishing sustainable tourism infrastructure. This framework provides a replicable model for traditional villages balancing economic growth with cultural preservation and environmental sustainability. Keywords: Sustainable tourism, digital heritage village, competitiveness strategy, SWOT-AHP analysis, community-based tourism.